UI/UX Instrument Validity and Reliability in Augmented Reality Geometry Learning with Hand Gestures Recognition - Dyah Susilowati; Dian Syafitri Ch.; Helna Wardhana; Sultan Fahrurazy (Upgrade : Jurnal Pendidikan Teknologi Informasi, 2026)
The implementation of Augmented Reality learning media in authentic educational contexts requires a rigorous instrument to assess usability, interaction quality, user satisfaction, and learning support. This study aimed to examine the validity and reliability of a User Interface/User  Experience instrument used to evaluate augmented reality-based geometry learning media integrated with hand gesture recognition. This study employed a Research and Development approach, which focused on instrument testing conducted as part of the product evaluation phase. Content validity was established through expert assessment, followed by construct validation using Confirmatory Factor Analysis. The analysis demonstrated an excellent measurement model, with a Comparative Fit Index of 1.000, Root Mean Square Error of Approximation of  0.000, and Goodness of Fit Index of 0.995. Reliability analysis produced coefficients of 0.959 for the User Interface construct, 0.935 for User Experience, and 0.968 for the complete instrument, indicating strong internal consistency. These findings indicated that the instrument achieved a high level of validity and satisfactory reliability, demonstrating its appropriateness and consistency for evaluating user experience in interactive learning environments. The study provides a psychometrically robust evaluation instrument that can be used to systematically assess the quality of Augmented Reality-based interactive geometry learning media and support more credible evaluation of user interaction and learning experiences.